From Isolation to Resistance: Exploring the Duality of Audience Engagement in Collective Spaces in Political Arts and Social Movements - Shokri, Homa (Taideyliopiston Teatterikorkeakoulu, 2024)
This thesis explores the interplay between technology, politics, and artistic expression in the digital era, focusing on contemporary performance art and its capacity to initiate societal dialogue and change. It investigates how performance art represents complex societal issues and examines the thin line between personal interpretation and the spread of propaganda. The research highlights the often-inadvertent continuation of colonial ideologies and biases against marginalized communities in these artistic endeavors. By delving into the consequences of ignorance, entrenched stereotypes, and prejudicial attitudes, the thesis addresses the ability of performance art to connect with diverse audiences and highlight stories often overlooked by mainstream media and propagandistic narratives. Additionally, various instances of political performances in public spaces across different countries, executed by both artists and non-artists, will be highlighted. The objective is to explore comparisons and distinctions between these acts, examining their relationship with audience engagement, and assessing their influence on social and expanded media platforms. A significant portion of this study analyses the inclusive portrayal of politically charged themes through socially engaged art, emphasizing the effects and implications of such representations. It further assesses the role of performance art in engaging non-professional audiences and its trans-formative potential in shaping public participation. The analysis covers themes such as state of war, political turmoil, and the experiences of displaced persons, aiming to re-imagine and preserve their stories. Beyond simply reporting on contemporary and historical political events, this thesis critically examines these events' ongoing impact on today's society.
Keywords: Socially engaged art; Reenactment; Political narratives; Colonial ideologies; Expanded media; Bodily presence; Public space; Videos; performanssi; yleisö; esitystaide; poliittinen taide; fi=ohjaus|sv=regi|en=Directing|